Global Patterns and Emerging Challenges of Human Monkeypox Virus: An In-Depth Narrative Review and Analysis (Bangladesh Journal of Medical Microbiology, 2025)
Monkeypox, caused by the monkeypox virus (MPXV), has reemerged as a notable public health issue, mostly because of the reduced immunity resulting from the cessation of smallpox immunization. The 2024 outbreaks in South Africa and Pakistan highlight the virus's ability to spread outside its usual areas, due to reasons such as more international travel, urban growth, and closer contact between humans and animals. This narrative review provides a comprehensive summary of the virus's epidemiology, clinical signs, transmission mechanisms, and therapeutic techniques. Additionally, it emphasizes important topics for future investigation, such as the need to observe viral changes over time, assess the prolonged efficacy of current vaccinations, and comprehend the environmental factors that impact viral spread. The results of this study are crucial for informing international health strategies that seek to avoid future outbreaks and strengthen global health protection in an ever more linked world.Bangladesh Journal of Medical Microbiology, July 2024;18(2):120-130